Phenol-Soluble Modulins From Staphylococcus aureus Biofilms Form Complexes With DNA to Drive Autoimmunity - Grando, Kaitlyn; Nicastro, Lauren K.; Tursi, Sarah A.; De Anda, Jaime; Lee, Ernest Y.; Wong, Gerard C. L.; Tükel, Çağla (Frontiers in Cellular and Infection Microbiology, 2022)
The bacterial amyloid curli, produced by Enterobacteriales including Salmonella species and Escherichia coli, is implicated in the pathogenesis of several complex autoimmune diseases. Curli binds to extracellular DNA, and these complexes drive autoimmunity via production of anti-double-stranded DNA autoantibodies. Here, we investigated immune activation by phenol-soluble modulins (PSMs), the amyloid proteins expressed by Staphylococcus species. We confirmed the amyloid nature of PSMs expressed by S. aureus using a novel specific amyloid stain, (E,E)-1-fluoro-2,5-bis(3-hydroxycarbonyl-4-hydroxy) styrylbenzene (FSB). Direct interaction of one of the S. aureus PSMs, PSMα3, with oligonucleotides promotes fibrillization of PSM amyloids and complex formation with bacterial DNA. Finally, utilizing a mouse model with an implanted mesh-associated S. aureus biofilm, we demonstrated that exposure to S. aureus biofilms for six weeks caused anti-double-stranded DNA autoantibody production in a PSM-dependent manner. Taken together, these results highlight how the presence of PSM-DNA complexes in S. aureus biofilms can induce autoimmune responses, and suggest an explanation for why bacterial infections sometimes correlate with autoimmunity.